TEORI MAQASHID SYARI'AH PERSPEKTIF IBNU ASHUR - Toriquddin, Moh. (ULUL ALBAB Jurnal Studi Islam, 2013)
Ibnu Ashur is a contemporary figure of maqasid syariah which born in Tunisia. He was complement and continues of maqasid concept which previously created by  imam al Shatibi, al Ghazali, Izzudin bin Abd. Salam, Ibnu Taymiyah, Ibnu Qayyim al Jauziyah, and another. By Ibnu Ashur, maqasid syariah easily practice in contemporary problems so that Islamic law still suitable with period or be up to date or in Arabic we can call salihun li kulli zaman wa al makan. There are few reform used by Ibnu Ashur in maqasid syariah for instance all discipline law are good characteristic is muamalah (transaction) or ibadah (religious service), all has illat (reason). For implementation maqasid theory by three steps: maqam khitab al syar’iy (situation dan condition of khitab syar’iy), al tamyiz baina al wasilah wa al maqshud (differentiate between infrastructure and purpose), istiqra’ (induction). Maqasid syariah theory by Ibnu Ashur however, globallly based on maqashid al ammah and maqashid al khasah. However, foundation thought for decide maqasid using by fitrah, maslahah, and ta’lil. For knowing something that has benefit or not, he was classified it by three categories benefit for community, benefit for group or person, and realize necessary.